Growth performance of neonatal Holstein heifers fed acidified waste milk containing essential oil blend and encapsulated butyrate alone or in combination - Ting Liu; Zhihao Luo; Peng Li; Shuru Cheng; Jianping Zhu; David.P. Casper (Journal of Dairy Science)
ABSTRACT: Previous research demonstrated the growth-promoting benefits of an essential oil and oligosaccharide blend (Stay Strong, Ralco, Inc.; EO) or an encapsulated sodium butyrate (C4; Ultramix GF, Adisseo, Inc.) fed to neonatal calves. The possibility exists that these technologies may be additive based on their individual mechanisms of action. The study objective was to evaluate EO and C4 alone or in combination when fed to Holstein heifers raised on a commercial Chinese dairy operation. Sixty-four heifers were blocked by calving day and randomly assigned to 1 of 4 treatments (n = 16/treatment) using a randomized complete block design. Treatments were: (1) Control: CON; milk fed 3×/d; (2) EO added to the milk at the rate of 1.50 g/d per head; (3) C4 added to the milk at 1.70 g/d per head; and (4) E4: EO and C4 added to the milk at the rates of 1.50 and 1.70 g/d per head, respectively. Heifers were fed acidified waste milk using an increasing- and decreasing-phase feeding program with weaning on d 56 for a 70-d experiment. Heifer birth weight was a significant covariate with heifers fed EO, C4, and E4, demonstrating greater BW (42.4, 47.0, 46.6, and 48.0 kg for CON, EO, C4, and E4, respectively) gains and ADG (605.0,672.5, 665.7, and 686.7 g/d, respectively) compared with heifers fed CON. Calf starter intake (0.558, 0.584, 0.692, and 0.624 kg/d, respectively) was greater for heifers fed C4 compared with heifers fed CON, with heifers fed EO and E4 being intermediate and similar. Feed conversions (0.439, 0.480, 0.444, and 0.477 kg/kg, respectively) were greater for calves fed EO and E4 compared with calves fed CON. Total days of fecal score = 0 was greater for heifers fed EO and lowest for heifers fed E4, with heifers fed CON and C4 being intermediate. Gains in body length and hip width were greater for heifers fed EO compared with heifers fed CON, C4, and E4. Total-tract apparent fiber (NDF and ADF) digestibility was greater in heifers fed EO and C4, intermediate for heifers fed E4, and lowest for heifers fed CON. Heifers fed EO demonstrated lower fecal Salmonella counts compared with heifers fed CON, C4, and E4. Heifers fed EO and C4 demonstrated greater blood serum total volatile fatty acid concentrations (9.75, 12.91, 11.22, 10.89 µM, respectively, for CON, EO, C4, and E4) compared with heifers fed CON, with heifers fed E4 being intermediate and similar. Heifers fed EO, C4, and E4 demonstrated greater growth performance, but the combination of EO and C4 did not further improve growth performance.